Russia and Ukraine in “Mazepa’s Shadow”: Caught Between Disintegration and Integration - JiEun Sim (Journal of Eurasian Studies)
This study examines the transformation of the cultural and political mythology surrounding Ivan Mazepa, a historical figure whose legacy is interpreted in fundamentally different ways by Ukraine and Russia. In Russian imperial narratives, Mazepa is characterized as a symbol of treachery, while in Ukrainian nationalist discourse, he embodies ideals of freedom and sovereignty. His persona also achieved international prominence in 18 th - and 19 th -century Europe, notably through Romantic literature and music, launching the phenomenon referred to as Mazepiana. The article outlines the evolution of Mazepa’s “artistic shadow” in the European cultural tradition before analyzing his “political shadow” relative to Ukraine and Russia. Particular attention is given to the resurgence of Mazepa’s image in Ukrainian public consciousness after 1991, with an emphasis on key events such as the 2009 tricentennial of the Battle of Poltava, Russia’s annexation of Crimea in 2014, and the 2022 full-scale invasion. Mazepa is positioned not merely as a symbolic figure, but as an active force in shaping the enduring historical dynamics of disintegration and integration in the Russia-Ukraine relationship. His influence continuously informs political narratives, national memory, and cultural identity, acting as a unifying symbol for Ukrainian sovereignty while remaining a focus of strong Russian criticism. As a figure whose significance endures across generations, Mazepa’s role highlights the persistent influence of myth in shaping post-Soviet identities.